Is concern about young people's anti-social behaviour associated with poor health? cross-sectional evidence from residents of deprived urban neighbourhoods - Egan Matt; Bond Lyndal; Kearns Ade; Tannahill Carol (BMC, 2012)
Abstract Background Young people in disadvantaged neighbourhoods are often the focus of concerns about anti-social behaviour (ASB). There is inconsistent evidence to support the hypothesis that perceptions of ASB (PASB) are associated with poor health. We ask whether perceptions of young people's ASB are associated with poor health; and whether health, demographic and (psycho)social characteristics can help explain why PASB varies within disadvantaged neighbourhoods (Glasgow, UK). Methods Regression analysis of survey data exploring associations between perceiving teenagers hanging around to be a serious neighbourhood problem and SF-12v2 mental and physical health scores (higher = better), including adjustment for demographic characteristics. Further analysis explored associations with self-reported measures of health service use, psychosocial characteristics of homes and neighbourhoods and social contacts. Results 6008 adults participated (50% response) and 22% (n = 1,332) said teenagers were a serious neighbourhood problem (the most frequently reported local problem). Demographic characteristics associated with perceiving serious teenager problems included regular health service use, age (inverse relationship), financial problems and living with children. Lower SF-12v2 physical health scores were associated with perceiving teenager problems after adjustment for demographic variables (OR 0.98; 95%CI 0.97,0.99; p = < 0.001), whilst adjusted findings for mental health scores were less conclusive (OR 0.99; 95%CI 0.98,1.00; p = 0.103). Further analysis suggested that perceiving teenager problems was more strongly associated with a number of self-reported psychosocial factors: e.g. lacking social support, < weekly family contacts, poor neighbourhood safety, low trust in neighbours, neighbourhood perceived to be a barrier to self-esteem, and neighbourhood decline. Conclusions Given the evidence we found of weak and small associations between PASB and health, we caution against assuming that tackling concern about teenagers' ASB will lead to substantial public health gains in disadvantaged areas. Although the findings do not present a compelling case for making PASB a public health priority, it is still important to address concerns about young people's ASB. Reasons for doing so may include improving social cohesion, reducing fear and isolation, and improving the general quality of people's lives - particularly in neighbourhoods burdened by multiple disadvantages. Future research should evaluate interventions that attempt to reduce PASB in disadvantaged areas. Findings from this study could help inform the targeting of such interventions.